Perbedaan produksi dan pendapatan usaha penangkapan ikan dengan alat tangkap sero berdasarkan lokasi pemasangan sero Kelurahan Tondonggeu Kecamatan Nambo Kota Kendari - Yahya, Zulkifli; Piliana, Wa Ode; Annaastasia, Nurhuda; Siang, Roslindah Daeng (Universitas Halu Oleo, 2025)
The research was carried out in Tondonggeu Village, Nambo District, Kendari City. The aim of this research is to determine the production produced, the profits obtained, and determine the differences in production and profits from sero fishing gear based on the location of the sero installation. This research uses interview, observation, documentation and literature study methods. The data used are primary and secondary data. The research results show that the amount of production produced in November from sero fishermen based on the location of the sero installation in areas around mangroves was 99 kg/month, areas around coral 75 kg/month and areas around seagrass 81 kg/month. The profit obtained by sero fishermen in November based on the location of the sero installation in areas around mangroves was IDR 2,564,280/month, in areas around coral it was IDR 2,092,091/month, and in areas around seagrass it was IDR 2,084,863/month.